Modeling and simulation of train movements under scheduling and control for a fixed-block railway network using cellular automata. (June 2013) - Zhou, Yonghua; Mi, Chao
The dynamics of train movements is not only determined by the control strength of the train, but also by the interdependence between trains and the scheduling command that specifies the allowable movement distance and speed. This paper attempts to propose a generalized simulation model of train movements using cellular automata so that the scheduling commands are incorporated into the model. Based on the concept of instantaneous movement authority, the proposed model generally decomposes the entire trip into a series of movements on each block section with speed limits at the start and endpoints of, as well as within, the section. It realizes the dynamic speed updates analogous to the feedback adjustments of realistic train movements, and describes both the dynamics of the train itself and the interactions between trains with adjustable parameters. The control strategies are reflected in the configurations of the acceleration and the deceleration. The autonomous, restrictive and synergistic aspects of train movements are completely represented. The model and the simulation algorithm are applied to simulate the train movements with and without the scheduling commands. The observed phenomena can be replicated, and the rationality of simulation results has been analyzed about the speed updates and the performances under the typical scheduling strategies. The proposed simulation model can facilitate the establishment of measures to maximize the transport efficiency of the railway network.